ANALISIS ELASTO PLASTIK PADA STRUKTUR PORTAL DENGAN METODA ELEMEN HINGGA - Anita Sida Butar, Ros
This thesis deals with theoretical elasto-plastic determination of ultimate loads, displacements, and distribution of plastic region in beam and framed structural systems, based on a finite element formulation. Pointwise determination of plastic conditions based on Tresca and von Mises, is modified to an elementwise determination scheme to account for the propagation of plastic regions. Eight node isoparametric element type is used in the analysis. Computational scheme is cast in a computer program written in Fortran language and run on IBM Compatible personal computer. Results obtained from the application of the method are discussed and compared to available exact solutions in which propagation of plastic regions is not taken into account